2020
DOI: 10.4236/psych.2020.119087
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Effects of the Gardening Activity on Mother and Their Infant: Preliminary Evidence from an Exploratory Pilot Study

Abstract: The Gardening activity is regarded as effective in improving psychological function. However, the psychological effects of the infant from mothers who engage in gardening activity are not well known. This study conducted an exploratory pilot study to confirm the psychological effects of the gardening activity on mother and their infant. Fifteen postpartum women with infants under one-year-old participated in this study. They participated in eight gardening activities. This study asked mothers questions about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The study results show that middle-aged women spent time cooking, gardening, and pets caring as relaxation activities that were less time-consuming and inexpensive. This result is consistent with studies that have shown activities such as cooking and gardening increase personal life satisfaction, positively affect psychological health, reduce stress, increase self-confidence, and increased cognitive function (Gonzalez et al, 2010;Wood et al, 2016;Eriksson et al, 2010;Kotozaki, 2020). Gardening is one of the most popular ways to interact with nature, and in many countries, it is considered a popular relaxing activity, and even a form of therapy for mental health issues (Soga, Gaston &Yamaura, 2017;Cheng et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…The study results show that middle-aged women spent time cooking, gardening, and pets caring as relaxation activities that were less time-consuming and inexpensive. This result is consistent with studies that have shown activities such as cooking and gardening increase personal life satisfaction, positively affect psychological health, reduce stress, increase self-confidence, and increased cognitive function (Gonzalez et al, 2010;Wood et al, 2016;Eriksson et al, 2010;Kotozaki, 2020). Gardening is one of the most popular ways to interact with nature, and in many countries, it is considered a popular relaxing activity, and even a form of therapy for mental health issues (Soga, Gaston &Yamaura, 2017;Cheng et al, 2010).…”
Section: Discussionsupporting
confidence: 83%
“…Another study [49] found a 12-month gardening physical activity intervention was able to restore attention in participants. Several studies to date showed that low-to-moderate intensity gardening activity, such as making vegetable gardens or digging, weeding, and planting is associated with memory gains in elderly individuals.…”
Section: Gardening Physical Activity Improves Cognitive Functionmentioning
confidence: 99%
“…Additionally, the participants reported significant improvement in their daily activities and overall quality of life, as assessed by the World Health Organization Quality of Life-Brief (WHOQOL-BREF) scale, after the gardening intervention. In another study [49], researchers demonstrated the benefit of a 12-month gardening intervention on stress regulation among mental health service users. Similar support was found among individuals with known mental health, heart conditions, and postpartum women, older people with dementia [40,53,55,56].…”
Section: Self-reported Assessmentsmentioning
confidence: 99%
“…Visiting a natural environment such as a garden, children’s farm, a forest, or park can be supportive to families. Studies in shelters as well as in other living places have indicated that natural environments near a family’s living place can be used as a safe and engaging place for family activities, where parents can find fun and unconstrained ways to interact with their children ( Ashbullby et al, 2013 ; Izenstark et al, 2016 , 2021 ; Cameron-Faulkner et al, 2018 ; Millican et al, 2019 ; Kotozaki, 2020 ; Rantala and Puhakka, 2020 ; Peters et al, 2020a ; Varning Poulsen et al, 2020 ). Such positive moments in nature are associated with stress reduction in parents ( Razani et al, 2018 ; Kotozaki, 2020 ) and responsive interactions between parent and child ( Cameron-Faulkner et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in shelters as well as in other living places have indicated that natural environments near a family’s living place can be used as a safe and engaging place for family activities, where parents can find fun and unconstrained ways to interact with their children ( Ashbullby et al, 2013 ; Izenstark et al, 2016 , 2021 ; Cameron-Faulkner et al, 2018 ; Millican et al, 2019 ; Kotozaki, 2020 ; Rantala and Puhakka, 2020 ; Peters et al, 2020a ; Varning Poulsen et al, 2020 ). Such positive moments in nature are associated with stress reduction in parents ( Razani et al, 2018 ; Kotozaki, 2020 ) and responsive interactions between parent and child ( Cameron-Faulkner et al, 2018 ). For parents in shelters specifically, experiences in a natural environment have been associated with parents’ experiences of connectedness with their child, autonomy in making parenting decisions, and competence in their parenting practice ( Peters et al, 2020a , b , 2021 ).…”
Section: Introductionmentioning
confidence: 99%